Lesões epiteliais malignas da conjuntiva e recidiva tumoral - Estudo retrospectivo - Schellini, Silvana Artioli [UNESP]; Matai, Olívia [UNESP]; Shiratori, Claudia [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Oliveira Júnior, Batista de [UNESP]; Padovani, Carlos Roberto [UNESP] (My University, 2005)
Purpose: To evaluate the conjunctival epithelial malign lesions carriers and the recurrence rate using exeresis and radiotherapy. Methods: A retrospective study was conducted observing 52 conjunctival epithelial malign lesions carriers treated from 1989 by 2003. The subjects were assessed to evaluation according: age, gender, time of start, classification of the lesion and recurrence rate. The lesion were surgically removed and radiotherapy was indicated when the exeresis was incomplete. Results: The majority of the patients were male, with 61 year old median age, white. The conjunctival squamous carcinoma was presented in 86,5% of the patients. The recidive rate was 11,5%, happened between 1 to 60 month postoperative. Conclusion: according our results the conjunctival epithelial malign lesions were more often observed in older, males and whites. The majority of the patient had conjunctival squamous carcinoma (86,5%). The recidive rate after exeresis and radiotherapy in patients with incomplete exéresis was 11,5%.
Malign epithelial conjunctival lesions and tumor recidive - A retrospective study
Keywords: Carcinoma in situ; Carcinoma, squamous cell; Carcinoma/radiotherapy; Carcinoma/therapy; Conjunctival neoplasms/therapy; Recurrence; Retrospective studies